Knowledge and Attitude on Febrile Seizure among Mothers with Under-Five Children - Syahida, Jihan Alifa; Risan, Nelly Amalia; Tarawan, Vita Murniati (Althea Medical Journal, 2016)
Background: Febrile seizures frequently occur in children under 5 years old and usually create fear and anxiety among parents. Poor understanding of febrile seizure among parents contributes to mismanagement of seizure. The objective of this study was to identify the knowledge and attitude on febrile seizure among mothers of under five children.Methods: This descriptive community-based survey comprised of 96 mothers with under 5 children who were chosen through randomization. This survey was, conducted in Hegarmanah Village, Jatinangor, West Java, Indonesia in October 2013. Data were collected using a questionnaire and analyzed using frequency analysis.Results: Fifty nine respondents (61%) considered that high fever in their children will result in seizure and 63 mothers (65%) stated that this condition was a life-threatening situation which could lead to brain damage (50%) and paralysis (50%). There were some respondents who would manage seizure by shaking (27%) or holding the child tightly during seizure (22%) and putting spoon into the children mouth (59%). Sixty respondents (62.5%) prevented febrile seizure by giving them coffee.Conclusions: Knowledge and attitude regarding febrile seizure is good, but the knowledge and attitude towards the outcome and what to do during febrile seizures occasion are still poor. [AMJ.2016;3(4):649â54]Â DOI:Â 10.15850/amj.v3n4.954